Powdered activated carbon – membrane bioreactor operated under intermittent aeration and short sludge retention times for micro-polluted surface water treatment. (August 2015) - Shao, Senlin; Qu, Fangshu; Liang, Heng; Li, Kai; Yu, Huarong; Chang, Haiqing; Li, Guibai
Abstract: Long sludge retention time (SRT) and continuous aeration are generally adopted in powdered activated carbon – membrane bioreactor (PAC-MBR) process for micro-polluted surface water treatment. However, in this study, the performance of a pilot-scale PAC-MBR under intermittent aeration and short SRTs (2, 4, 6, and 8 d) was investigated. The settling characteristics of sludge and the decay of dissolved oxygen (DO) concentration in the mixed liquor were examined. The results showed that intermittent aeration with proper aeration intervals barely reduced the removal efficiency of pollutants, due to the low DO consumption in the bioreactor and the low settling velocity of the sludge (mostly at the range of 0.04–0.08 m min −1 ). High concentration ammonia (∼3 mg L −1 ) could be effectively removed even at a fairly short SRT (6 d). As the SRT increased, the removal efficiencies of organic matter and ammonia increased, but the membrane fouling aggravated correspondingly. The successful adoption of intermittent aeration and short SRTs in the pilot-scale PAC-MBR implied that the results could be extrapolated to full-scale applications to reduce operating costs and alleviate membrane fouling. Highlights: Intermittent aeration with proper intervals could be adopted in PAC-MBR. Pollutant removal and membrane fouling were increased as the SRT increased. Ammonia could be effectively removed at a relatively short SRT (6 d).